CONCEPT AND TYPES OF DISCRIMINATION IN LABOR LAW - Вишновецька, Світлана Василівна; Дорошенко, Тетяна Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: clarify the concept of discrimination in employment law, to identify the main types of employment discrimination and identify areas of countering any of its manifestations in the use of hired labor. Methods: analysis, synthesis, generalization, comparison and others. Results: recognized the need to normatively define the formal and legal arteries of the degeneration of discrimination not only in physiological, gender and socio-cultural aspects, but also professional and qualification. Discussion: enshrining in labor legislation the concept of direct and indirect discrimination, which will protect employees from the negative consequences of externally neutral actions of the employer, which have discriminatory consequences. The development of a competitive environment and an increase in the employer’s interest in reducing costs contribute to the spread of discrimination in employment. Discrimination in labor law is a situation in which a person on anti-discrimination grounds (race, color, political, religious and other beliefs, sex, age, ethnic and social origin, citizenship, marital and property status, place of residence, health status, disability, pregnancy and maternity, sexual orientation, lifestyle, language, appearance), not related to business qualities, is subject to restrictions, differences or exceptions in the recognition, exercise or use of labor rights in any form that leads to a violation of equal opportunities in the field of labor, except in cases where such restriction of rights, establishment of differences or exceptions has a legitimate, objectively justified purpose, the ways to achieve which are appropriate and necessary. It was found that according to the degree of openness of the employer’s actions, discrimination is divided into direct and indirect. It was found that the most common types of discrimination in the labor market are discrimination on the grounds of sex, on the basis of disability, on the basis of age. It is concluded that discrimination occurs where equal opportunities in the field of labor are violated, ie equal conditions for the realization of equal rights of workers. The only exception may be a lawful restriction of labor rights due to the requirements inherent in this type of work, established by law and related to the special care of the state for persons in need of increased social and legal protection. Such a restriction must have a legitimate, objectively justified purpose and be established in a lawful manner.